Kajian Fenomena Overtourism di Kawasan Wisata di Bali dan Pengelolaannya - Hm, Fhaaris; Hulu, Meitolo (Jurnal Ilmiah Global Education, 2025)
The phenomenon of overtourism has become a significant issue in tourism management in Bali, particularly in areas such as Canggu, Kuta, Ubud, Kintamani, and Penglipuran Village. The post-pandemic surge in tourist arrivals has brought positive economic impacts, but it has also exerted pressure on the environment, infrastructure, and the social and cultural life of local communities. This study employs a descriptive qualitative method, with data collected through in-depth interviews, field observations, and documentation. The primary aim of this research is to examine the condition of overtourism in Bali and analyze the management efforts undertaken by local governments. The findings indicate that the management of overtourism remains suboptimal. There is a need for the implementation of the carrying capacity concept and visitor management strategies to prevent further degradation. The recommendations provided include limiting the number of tourists, ensuring a more even distribution of visits, involving local communities in policy-making, and strengthening sustainable tourism regulations.